2016
DOI: 10.1177/1747493016677983
|View full text |Cite
|
Sign up to set email alerts
|

IRMA study: Prevalence of subdiaphragmatic visceral infarction in ischemic stroke and atrial fibrillation

Abstract: Background Occult atrial fibrillation (AF) may, in part, explain cryptogenic stroke. A 22% prevalence of subdiaphragmatic visceral infarction (SDVI) among patients with ischemic stroke (IS) due to AF has been reported, using abdominal MRI. We sought to assess the reproducibility of this method and to confirm that SDVI is more prevalent in cases of AF-caused IS than in IS of other etiologies. Methods In consecutive patients admitted to our hospital, we compared SDVI prevalence in three groups: patients with IS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
2
2
0
Order By: Relevance
“…[7][8][9] Furthermore, in reports limited to organs beneath the diaphragm, abdominal MRI within 1 week of ischemic stroke onset has revealed evidence of splenic or renal infarction in 14% of cases. 19 This study found almost the same in the frequencies reported in previous studies. What makes this study important is that it examined systemic embolism in the hyperacute phase of ischemic stroke.…”
Section: Discussionsupporting
confidence: 87%
“…[7][8][9] Furthermore, in reports limited to organs beneath the diaphragm, abdominal MRI within 1 week of ischemic stroke onset has revealed evidence of splenic or renal infarction in 14% of cases. 19 This study found almost the same in the frequencies reported in previous studies. What makes this study important is that it examined systemic embolism in the hyperacute phase of ischemic stroke.…”
Section: Discussionsupporting
confidence: 87%
“…Prior studies of abdominal magnetic resonance imaging in patients with cardioembolic stroke show a 20% prevalence of visceral infarcts. 3, 6 Our results build on these studies by demonstrating the prevalence of visceral infarction differs across ischemic stroke subtypes. We found no visceral infarcts among patients with lacunar stroke, supporting this stroke subtype as a distinct entity resulting from in-situ occlusion of the cerebral vasculature.…”
Section: Discussionsupporting
confidence: 65%
“…[120][121][122][123][124][125] In a study of 227 patients with acute-ischemic stroke, the prevalence of visceral infarct differed significantly by stroke type: 34.2% in cardioembolic strokes (95% CI: 7-44.6%), 23.9% in strokes of undetermined etiology (95% CI: 15.0-32.8%), and 12.5% for large-artery atherosclerotic strokes/small-vessel occlusions combined (95% CI: 1.8-23.2%) 124 ; this is consistent with prior studies. [120][121][122] Despite their frequency, the clinical significance, risk factors, and pathophysiology of visceral infarctions remain poorly understood. In cardioembolic stroke, atrial remodeling and impaired contractility contribute to blood stasis/endothelial injury, and visceral infarction is likely a clinical manifestation of the prothrombotic state.…”
Section: Fecal Incontinencementioning
confidence: 99%
“…120 121 122 123 124 125 In a study of 227 patients with acute-ischemic stroke, the prevalence of visceral infarct differed significantly by stroke type: 34.2% in cardioembolic strokes (95% CI: 7–44.6%), 23.9% in strokes of undetermined etiology (95% CI: 15.0–32.8%), and 12.5% for large-artery atherosclerotic strokes/small-vessel occlusions combined (95% CI: 1.8–23.2%) 124 ; this is consistent with prior studies. 120 121 122 Despite their frequency, the clinical significance, risk factors, and pathophysiology of visceral infarctions remain poorly understood. In cardioembolic stroke, atrial remodeling and impaired contractility contribute to blood stasis/endothelial injury, and visceral infarction is likely a clinical manifestation of the prothrombotic state.…”
Section: Known Gastrointestinal Complications Secondary To Acute Isch...mentioning
confidence: 99%